Malignancy Index Using Intraoperative Flow Cytometry is a Valuable Prognostic Factor for Glioblastoma Treated With Radiotherapy and Concomitant Temozolomide. Issue 3 (30th March 2018) - Saito, Taiichi; Muragaki, Yoshihiro; Shioyama, Takahiro; Komori, Takashi; Maruyama, Takashi; Nitta, Masayuki; Yasuda, Takayuki; Hosono, Junji; Okamoto, Saori; Kawamata, Takakazu
Abstract: BACKGROUND: Intraoperative prediction of radiochemosensitivity is desirable for improving the clinical management of glioblastoma (GBM) patients. We have previously developed an original technique for intraoperative flow cytometry (iFC) and defined a malignancy index (MI). OBJECTIVE: To determine whether MI correlates with prognosis in GBM patients who underwent the standard treatment protocol of radiotherapy and temozolomide administration. METHODS: The current study included 102 patients with GBM that had been newly diagnosed from 2010 to 2015 who underwent our iFC analysis and received the standard treatment protocol. We evaluated MI values in each patient, then statistically analyzed the relationship between MI and prognosis using survival analysis that include other clinicopathological factors (age, sex, Karnofsky performance status [KPS], extent of resection, second-line bevacizumab, O6-methylguanine-DNA methyltransferase [MGMT] status, MIB-1 labeling index, and mutation of the isocitrate dehydrogenase 1 gene [ IDH1 ]). RESULTS: Log-rank test revealed that age, KPS, extent of resection, MGMT status, IDH1 mutation, and high MI (≥26.3%) significantly correlated with overall survival. Multivariate analysis with Cox regression modeling identified MI as the most significant prognostic factor (hazard ratio = 2.246; 95% confidence interval = 1.347-3.800; P = .0019). MI showed strong correlation with IDH1 mutation status in chi-square test ( P = .0023). In addition, log-rank test revealed that MI affects overall survival more strongly in patients with IDH1 wildtype than those with IDH1 mutant. CONCLUSION: MI from an iFC study may help predict the prognosis in patients with GBM who receive the standard treatment. Survival can be related to sensitivity to radio-chemotherapy.